Fenomenologi Produk Lending Perbankan Syari’ah dalam Perspektif Maqashid Syari’ah - Ahsani Taqwiem; Kasuwi Saiban; Misbahul Munir (El-Aswaq: Islamic Economics and Finance Journal, 2021)
Defrayal or financing is funding provided by one party to another to support the planned investment, either by themselves or institution. In other words, the financing is funding incurred to support the planned investment. Financing terms in effect means that I believe, I trust. The word financing means (trust) that means financial institutions as sahib al-mal put their trust in someone to carry out the given mandate. The fund should be used properly, fairly, and must be accompanied by a bond and the terms are clear and mutually beneficial for both parties. Each financial institution has syari’ah philosophy to seek the pleasure of Allah. to obtain good in the world and the hereafter. Therefore, any activities of financial institutions which feared deviate from the guidance of religion should be avoided. In the implementation of the financing, Islamic bank must fulfill two very important aspects, namely: (1) syar’i aspect, where in each realization of financing to customers, the Islamic bank must be oriented to the Islamic Shariah; and (2) the economic aspect, which is still considering the gains, both for banks and for Shariah bank customers